Replication of patriarchal rule: on the gender and power relations in Yan Geling’s novels - Lim, Choon Bee; Liu, Xingyu (Penerbit Universiti Pendidikan Sultan Idris, 2024)
Many scholars believe that in her novels, Yan Geling’s creation of the “Earth Mother” female characters subverts traditional gender relations by rescuing males, thereby undermining the male-centered patriarchal culture. However, when examining the character relationships in Yan's novels from a feminist perspective, it can be observed that despite redeeming numerous males, the “Earth Mother” females remain a subjugated group under male power. Expanding from the perspective of the “Earth Mother” females, it can be further noted that, apart from the domination-subordination relationship between the sexes, even among the same sex, typical power relations of patriarchal systems are evident. This paper will explore the gender power relations among characters in Yan Geling’s works from three aspects: male-female, female-female, and male-male, to demonstrate the replication of patriarchal cultural power relations.